1994
DOI: 10.1021/bi00182a001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of the Ca2+-ATPase by Spermine and Other Polycationic Compounds

Abstract: The ATPase activity of the Ca(2+)-ATPase of skeletal muscle sarcoplasmic reticulum is inhibited by a variety of polyamines, including spermine, spermidine, and poly(arginine). The effects of spermine on the ATPase are highly specific. It has no effect on the affinity of the ATPase for Ca2+ or ATP, and no effect on the rate of phosphorylation by ATP. When the ATPase is phosphorylated with Pi in the presence of dimethyl sulfoxide at pH 6.0, and then dephosphorylation is induced by dilution in buffer at pH 7.5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
4
25
0
Order By: Relevance
“…Further, processing of A␤ (13) and other proteins (14,15) involved in neurodegenerative diseases seems to be associated with cholesterol-enriched membrane microdomains (lipid rafts) that can be isolated from neuronal plasma membranes (16) and other membranes based on their resistance to solubilization in nonionic detergents. Although the full-length A␤ contains 39 to 43 amino acid residues, it has been shown that the amyloid ␤-fragment 25-35 (A␤25- 35) represents the biologically active region of the full peptide and exhibits the same neurotoxic effect as the full-length peptide (17). Here, we relate changes in Ca 2ϩ -ATPase function in human brain affected by AD to effects of A␤ on the three types of Ca 2ϩ -ATPases.…”
mentioning
confidence: 96%
“…Further, processing of A␤ (13) and other proteins (14,15) involved in neurodegenerative diseases seems to be associated with cholesterol-enriched membrane microdomains (lipid rafts) that can be isolated from neuronal plasma membranes (16) and other membranes based on their resistance to solubilization in nonionic detergents. Although the full-length A␤ contains 39 to 43 amino acid residues, it has been shown that the amyloid ␤-fragment 25-35 (A␤25- 35) represents the biologically active region of the full peptide and exhibits the same neurotoxic effect as the full-length peptide (17). Here, we relate changes in Ca 2ϩ -ATPase function in human brain affected by AD to effects of A␤ on the three types of Ca 2ϩ -ATPases.…”
mentioning
confidence: 96%
“…Thapsivillosin A also binds to the ATPase with high affinity, to give a modified E2 state of the ATPase [26]. In the presence of Ca# + and ATP at pH 6.0, the ATPase was maximally phosphorylated (Table 1 ; [29]) ; labelling the ATPase with DMC had no effect on 4 2 − can bind to the ATPase, but only H 2 PO 4 − can phosphorylate it. Curve c also includes the effects of pH and Mg 2 + on the E1-E2 equilibrium for the ATPase, calculated using the parameters given in Lee et al [31].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other as yet unidentified proteins have been noted to exhibit the ability to effect phospholipid transbilayer movement (55,56). Thus which candidate flippase is active in HL-60s undergoing apoptosis and whether it, or modulators of its activity (60,61), interacts with polyamines is the goal of future studies. We note that several proteins, protein kinase CK2 (46,62) and the inward rectifier potassium channel (38,63,64), have binding sites for spermine and are specifically regulated by it, thus setting precedence for polyamine regulation of protein function.…”
Section: Discussionmentioning
confidence: 99%